THE INFLUENCE OF GREEN MARKETING TOWARDS PURCHASE INTENTION THROUGH BRAND AWARENESS (A STUDY ON LOVE, BEAUTY, AND PLANET) - Akhfiani, Lika (Jurnal Ilmiah Mahasiswa FEB, 2022)
This study aims to determine the influence of Love, Beauty and Plante’s Green Marketing on Purchase Intention and examine whether Brand Awareness has an effect as mediating role. This study is conducted in Malang, East Java. This type of research is descriptive research with a quantitative approach and questionnaire survey methods conducted on 150 respondents. The sampling using non-probability sampling method with purposive sampling technique. Data processing is done by using SmartPLS version 3.3. The implementation of Green Marketing on Love, Beauty and Planet is positively significant to increase customer’s Purchase Intention and Brand Awareness has shown to have a significant effect as a mediating role towards Purchase Intention. Keywords: Green Marketing, Purchase Intention, Brand Awareness